ETNOMATEMATIKA: KESENIAN TANJIDOR DI KELURAHAN CIJANTUNG DAN KAITANNYA DALAM PENERAPAN KONSEP MATEMATIKA - Syifa Najwa Putri; Ananda Muazizah; Fauzi Mulyatna (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Ethnomathematics is a science that studies the relationship between mathematics and culture. There are cultural elements in mathematics, for example traditional food, traditional buildings, regional dances, regional musical instruments and even regional musical arts which have mathematical concepts in them. The culture from which we can explore ethnomathematics is Betawi regional art, namely the tanjidor musical instrument which originates from Betawi. The aim of this researcher is to preserve cultural arts. This research uses a qualitative research method with an ethnographic approach model. The results of the research can show that the art of the Tanjidor musical instrument has several mathematical concepts for each instrument, namely the concept of size of the Tanjidor musical instrument, the concept of lines, the concept of flat shapes, the concept of space and the concept of numbers on the Tanjidor musical instrument.